Active Family Control And Company Performance: The Role Of Foreign Investment Moderation And Bank Deb - Perminas Pengeran (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This study was to examine the moderating role of foreign ownership and Bank debt on the influence of active family control toward the family firm performance. Based on purposive sampling techniques, this study used 18 family firms listed in Indonesia Stock Exchange (IDX), during the period of 2006-2011. The results of this study showed several important findings. Firstly, foreign ownership positively moderated the effect of active family control on profitability. Secondly, likewise, bank debt negatively moderated the effect of active family control on profitability. Thirdly, foreign ownership negatively moderated the effect of active family control on dividends payment. Finally, bank debt positively moderated the influence of active family control on dividends payment. These results revealed that the foreign ownership and bank debt serves as moderator on the relationship between active family control and financial performance.